(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2006)
The tragic end of the whole episode terminated in the satirical “situation ethics”. Despite the ongoing full-scale investigation by the police, the father of the girl connived with the rapist, forced her daughter to eat her statement, and she refused to identify the rapist. In return the father received Rs 200,000/- as “compensation money”, medical evidence was castrated, and the law was noose hanged on the bough of avarice and greed. The father made his action tailored to fit objective circumstances, the situation. He had been so full and determined in understanding what was right (for him) that he couldn’t visualize what was good (for her daughter and the society).